Technical Success, Midterm Primary Patency, and Factors Affecting Primary Patency of Subintimal Angioplasty Followed by Vasculomimetic Stenting for Trans-Atlantic Intersociety Consensus II C and D Femoropopliteal Arterial Disease—A Prospective Study - Joseph, Ansan; Valakkada, Jineesh; Ayappan, Anoop; Kannath, Santhosh; Shivanesan, Pitchai (Indian Journal of Radiology and Imaging, 2023)
Background The best option among the endovascular options in long, complex femoropopliteal (FP) lesions, and factors affecting the patency have yet to be well described. There are few studies describing the mid- and long-term patency of endovascular stents in long-segment FP occlusions.Aim This study aimed to determine the technical success and mid-term patency of subintimal angioplasty with vasculomimetic stenting in Trans-Atlantic Inter-Society Consensus II (TASC) C and D FP disease. The patient and imaging factors that affect primary patency were also analyzed.Methods and Materials A single-center prospective study was performed on 52 consecutive patients undergoing endovascular treatment for TASC C and D FP disease from 2017 to 2021. Angioplasty with stenting was performed in all patients and followed up for 36 months. Endpoints were primary patency rates and amputation-free survival of the limb. Kaplan–Meier curves were used to see patency rates and amputation-free survival rates.Results A total of 52 patients underwent stenting with a technical success rate of 100% if the sub-intimal arterial flossing with antegrade-retrograde intervention (SAFARI) technique was used. Primary stent patency at 6, 12, 18, 24, and 36 months was 89.8, 81.4, 76.2, 71.4, and 62.5%, respectively. Amputation-free survival was 98, 95.6, 91.8, and 85.7% at 12, 24, 30, and 36 months, respectively. Cox proportional regression analysis showed smoking and vessel wall calcium score more than 270 degrees as independent predictors of loss of primary patency (hazard ratio 0.35 confidence interval [CI]: 0.003–0.448) and 0.102 (CI: 0.022–0.47), respectively.Conclusion Subintimal angioplasty with vasculomimetic stent has good midterm patency in and amputation-free survival in long-segment FP occlusions. Smoking and severe vessel wall calcification adversely affect patency.
Keywords: peripheral arterial disease; TASC C and D FP disease; subintimal angioplasty; vasculomimetic stent